Pengaruh Gaya Kepemimpinan Birokrasi terhadap Kinerja Pegawai melalui Teamwork sebagai Variabel Intervening pada Dinas Kehutanan Provinsi Jambi (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
\ This study aims to analyze the influence of bureaucratic leadership style on employee performance with teamwork as an intervening variable at the Forestry Service of Jambi Province. Human resources are the main determinant of organizational success, particularly in public bureaucracies that demand effectiveness, discipline, and strong responsibility. Bureaucratic leadership, which emphasizes formal structure, rule compliance, and systematic work procedures, is believed to enhance efficiency but may also limit employee creativity and flexibility. In this context, teamwork becomes a crucial factor that strengthens the relationship between leadership and performance through enhanced collaboration, communication, and synergy among employees. This research employs a quantitative approach with an explanatory design. The population consists of 56 employees of the Forestry Service of Jambi Province selected using saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings indicate that bureaucratic leadership style has a positive and significant effect on both employee performance and teamwork. Furthermore, teamwork also has a positive and significant effect on performance and mediates the relationship between bureaucratic leadership and performance. The R-square results show that most of the variation in performance can be explained by bureaucratic leadership and teamwork. These findings highlight that the effectiveness of bureaucratic leadership is optimized when supported by strong teamwork. This study provides practical implications for public institutions to develop adaptive leadership strategies and foster a collaborative work culture to enhance employee productivity and organizational performance.